2010
DOI: 10.1080/01634372.2010.503984
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Access to Medicare Home Health Care: The Disparate Impact of Policy

Abstract: The Balanced Budget Act of 1997 dramatically decreased reimbursements for traditional Medicare home health patients. A multivariate analysis of Medicare Current Beneficiary Survey data showed that African American and "other" users experienced greater decreases in home care between 1996 and 1998 than did White users. These results suggest (a) race/ethnicity is an independent factor in determining service use post-BBA and (b) health policy has a disparate impact on minority older adults. Capitated payment syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Previous work suggests that changes in Medicare reimbursement policy influence service delivery patterns in the home health care setting, including reductions in services provided to frailer patients with greater health impairments. [13][14][15][16] Changes in reimbursement policy that were intended to reduce spending have led to large cutbacks in service delivery for patients who have greater cognitive, health, and functional impairments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work suggests that changes in Medicare reimbursement policy influence service delivery patterns in the home health care setting, including reductions in services provided to frailer patients with greater health impairments. [13][14][15][16] Changes in reimbursement policy that were intended to reduce spending have led to large cutbacks in service delivery for patients who have greater cognitive, health, and functional impairments.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Research has shown that policies decreasing Medicare's payments to home health care providers are linked to greater reductions in services for beneficiaries with greater functional, health, and cognitive impairments than in those for healthier beneficiaries with fewer functional and cognitive impairments. [13][14][15][16] These studies highlight the need to examine whether inefficiencies are present within the current Medicare reimbursement model that provide financial disincentives for serving the most vulnerable and clinically complex of the beneficiaries who receive home health care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of pre-and post-BBA Medicare data found significantly greater decreases in: number of users per 1,000 enrollees, intensity of service, level of agency reimbursement, number of non-skilled service visits, and length of service for non-White beneficiaries (Davitt & Kaye, 2010;McCall et al, 2001McCall et al, , 2003Murkofsky, Phillips, McCarthy, Davis, & Hamel, 2003). Davitt and Kaye (2010), based on a comprehensive set of control variables, suggest that race may be an independent and separate factor in the determination of service delivery post-BBA. Other studies found no differences by race/ethnicity in likelihood of home health use, number of visits, or length of service (Fitzgerald et al, 2006;Han, Remsburg, Lubitz, & Goulding, 2004;Liu, Long, & Dowling, 2003).…”
Section: Health Disparitymentioning
confidence: 93%
“…Other studies found no differences by race/ethnicity in likelihood of home health use, number of visits, or length of service (Fitzgerald et al, 2006;Han, Remsburg, Lubitz, & Goulding, 2004;Liu, Long, & Dowling, 2003). Limitations in these studies included: lack of controls for key predisposing and enabling factors (McCall et al, 2001); lack of controls for health or functional status (McCall et al, 2003); and no measure of SES (Liu et al, 2003;Murkofsky et al, 2003), only income and education (Davitt & Kaye, 2010). Likewise, analyses were conducted on limited racial/ethnic subgroups.…”
Section: Health Disparitymentioning
confidence: 98%